A Retrospective Study of Preconception and Pregnancy Behaviors Among Mothers of Stunted Infants - Nurul Qamarya; Erni Faturrahmah; Bela Santika Sandra (Jurnal EduHealth, 2024)
Stunting is a chronic nutritional problem influenced by various factors, including maternal behavior before and during pregnancy. Social environment, lifestyle, nutritional status, and maternal health history play significant roles in the incidence of stunting. This study aims to describe the behaviors of mothers during the preconception period and pregnancy who have children with stunting conditions. This research is a descriptive quantitative study with a retrospective approach. A total of 17 mothers with stunted toddlers in Monggonao Subdistrict, Bima City, in 2024 were selected using purposive sampling. Data were collected through questionnaires and interviews, then analyzed univariately and presented in frequency distribution tables. Most mothers did not smoke but were exposed to cigarette smoke as passive smokers both during preconception and pregnancy. As many as 58.8% regularly attended antenatal care, yet still had children with stunting. The majority (64.7%) consumed nutritious food during pregnancy, but not consistently and were limited by economic factors. A total of 47% of mothers had a history of comorbidities such as diabetes, asthma, heart disease, anemia, and chronic energy deficiency (CED). Exposure to cigarette smoke, inconsistent nutritional intake, and maternal health conditions are risk factors contributing to stunting, even among mothers who received antenatal care. A more holistic intervention approach is needed to prevent stunting starting before pregnancy.